Lightweight and high-ductility concrete and preparation method thereof

By using specific composition and modification treatment technology in concrete to form an ordered fiber network structure, the problem of difficulty in taking into account low density and high ductility is solved, and the effect of low density and high ductility of concrete is achieved.

CN118221407BActive Publication Date: 2025-02-21CHINA RAILWAY TUNNEL GROUP CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410397687.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-03
Publication Date
2025-02-21
Estimated Expiration
2044-04-03

AI Technical Summary

Technical Problem

The prior art is difficult to take into account both low density and high ductility characteristics in concrete, resulting in a significant reduction in mechanical properties when the density decreases.

Method used

Lightweight consisting of cement, fly ash, silica fume, fly ash hollow microbeads, water, sodium dodecyl beads, dodecyl dimethylbenzyl ammonium bromide solution and basalt fibers Highly ductile concrete controls the density and mechanical properties of concrete through surfactant modification and the formation of ordered fiber network structure.

Benefits of technology

The low density and high ductility of concrete are achieved, and the comprehensive performance of concrete is improved, including good compressive strength and tensile strain performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118221407B_ABST
    Figure CN118221407B_ABST
Patent Text Reader

Abstract

The invention discloses a lightweight high-ductility concrete and a preparation method thereof, which is composed of the following raw materials by weight: 1-1.2 parts of cement, 0.8-1 parts of fly ash, 0.16-0.2 parts of silica fume, 0.1-0.2 parts of fly ash hollow microspheres, 0.4-0.7 parts of water, 0.02-0.12 parts of sodium dodecylbenzenesulfonate solution, 0.03-0.14 parts of dodecyl dimethyl benzyl ammonium bromide solution, and 0.3-0.6 parts of basalt fiber. The preparation method solves the technical problem that concrete materials cannot take into account both low density and high ductility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete preparation, and in particular relates to a lightweight and high-ductility concrete and a preparation method thereof. Background Art

[0002] Lightweight and high ductility concrete is a special type of concrete with the characteristics of light weight, high strength and good crack resistance. Specifically, there are a large number of pores inside the lightweight and high ductility concrete, so its self-weight load is small and the degree of deformation is large. It is not easy to break under unexpected loads, thereby enhancing the safety of the concrete structure.

[0003] In order to reduce the density of concrete, it is usually prepared by adding foaming agents, etc., to form pores in the concrete to reduce the density of the concrete. However, the size and shape of the pores formed during the foaming process are difficult to control, resulting in a decrease in the density of the concrete and a significant decrease in the mechanical properties. In order to improve the mechanical properties of concrete, fine aggregate and fiber materials are usually added to the concrete material to minimize the pores and microcracks in the material, thereby improving the mechanical properties of the concrete. However, fine aggregate and fiber materials will significantly increase the density of the concrete. How to make concrete materials have both low density and high ductility is a difficulty in the field of concrete preparation. Summary of the invention

[0004] The purpose of the present invention is to provide a lightweight and high-ductility concrete and a preparation method thereof, which solves the technical problem that concrete materials cannot have both low density and high ductility properties.

[0005] The present invention adopts the following technical scheme: a lightweight and high-ductility concrete, which is composed of the following raw materials, measured by weight: 1-1.2 parts of cement, 0.8-1 parts of fly ash, 0.16-0.2 parts of silica fume, 0.1-0.2 parts of fly ash hollow microspheres, 0.4-0.7 parts of water, 0.02-0.12 parts of sodium dodecylbenzene sulfonate solution, 0.03-0.14 parts of dodecyl dimethyl benzyl ammonium bromide solution, and 0.3-0.6 parts of basalt fiber.

[0006] Furthermore, the concentration of the sodium dodecylbenzene sulfonate solution is 250-300 mg / L.

[0007] Furthermore, the concentration of the dodecyldimethylbenzylammonium bromide solution is 200-280 mg / L.

[0008] Furthermore, the basalt fiber has a length of 16-25 mm, a diameter of 0.2-0.5 mm, and a tensile strength of 2000-3800 MPa.

[0009] The present invention also discloses a method for preparing the above-mentioned lightweight and high-ductility concrete, and the preparation method is as follows:

[0010] Step S1, weighing various raw materials, mixing fly ash, silica ash and basalt fiber, and stirring evenly to obtain composite filler A;

[0011] Step S2, mixing the sodium dodecylbenzene sulfonate solution with the composite seasoning A in step S1, adding one eighth of water, stirring evenly and drying to obtain a modified composite filler B;

[0012] The dodecyl dimethyl benzyl ammonium bromide solution is mixed with the fly ash hollow microspheres, and one eighth of water is added, stirred evenly and dried to obtain modified fly ash hollow microspheres C;

[0013] Step S3, mixing the modified composite filler B and the modified fly ash hollow microspheres C in step S2, adding cement and three quarters of water, stirring evenly, and obtaining a lightweight and high-ductility concrete.

[0014] Furthermore, the drying temperature in step S2 is 30-80° C. and the drying time is 3-8 hours.

[0015] Furthermore, the stirring method in step S1 is dry mixing, the equipment is a drum dry powder mixer, the stirring speed is 100r / min, and the time is 20min.

[0016] Furthermore, the mixing method in steps S2 and S3 is wet mixing, the equipment is a forced flat-mouth mixer, the mixing speed is 80 r / min, and the time is 30 min.

[0017] The beneficial effects of the present invention are as follows: 1. The surfaces of the modified fly ash, silica ash and basalt fibers are activated, and materials with the same electrical properties repel each other, separate from each other, and are not easy to agglomerate; the modified fly ash, silica ash, basalt fibers and the modified fly ash hollow microbeads are attracted to each other by electric charges, and the modified fly ash, silica ash and basalt fibers tend to surround the modified fly ash hollow microbeads, and similarly, the modified fly ash hollow microbeads also tend to surround the modified fly ash, silica ash and basalt fibers to form an ordered fiber network structure. 2. By adding fly ash hollow microbeads with controllable pore size, the size of the pores inside the concrete is effectively controlled to control the density of the concrete; at the same time, by adding basalt fibers, the ductility of the concrete is improved. 3. By introducing surfactant groups, the fiber dispersion is improved, so that the fiber distribution added to the concrete is more uniform, forming a three-dimensional multi-directional fiber network, thereby improving the toughness of the concrete. 4. The orderly assembly of aggregates and fibers is achieved through surfactant modification, and the formed orderly fiber network structure has the characteristics of light weight and good ductility, which improves the comprehensive performance of concrete. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 SEM for lightweight and highly ductile concrete;

[0019] Figure 2 Density diagrams of examples and comparative examples;

[0020] Figure 3 The compressive strength and tensile strain diagrams of the embodiments and comparative examples are shown in FIG. DETAILED DESCRIPTION

[0021] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0022] The invention discloses a lightweight high-ductility concrete, which is prepared from the following raw materials in parts by weight: 1-1.2 parts of cement, 0.8-1 parts of fly ash, 0.16-0.2 parts of silica fume, 0.1-0.2 parts of fly ash hollow microspheres, 0.4-0.7 parts of water, 0.02-0.12 parts of sodium dodecylbenzene sulfonate solution, 0.03-0.14 parts of dodecyl dimethyl benzyl ammonium bromide solution, and 0.3-0.6 parts of basalt fiber.

[0023] In the present invention, the cement is P.O52.5 silicate cement, with a specific surface area greater than 300-500m 2 / kg, magnesium oxide content is less than 5%, sulfur trioxide content is less than 3.5%, initial setting time is greater than 100min, and final setting time is less than 300min.

[0024] The fly ash is water-washed Class C Grade I fly ash of national standard, with a density of 1.9-2.5g / cm3 and a specific surface area of ​​300-400m 2 / kg.

[0025] Fly ash hollow microspheres are fly ash hollow microspheres that have been washed and ball-milled, with a mesh size of 40-60 mesh, a particle size of 140-200μm, and a specific surface area of ​​350-450m 2 / kg.

[0026] Silica fume needs to be washed with water, with an average particle size of 0.1-0.5μm and a specific surface area of ​​300-420m 2 / kg, the content of silicon dioxide in silica ash is greater than 80%.

[0027] The concentration of the sodium dodecylbenzene sulfonate solution is 250-300 mg / L, and the most preferred concentration is 280 mg / L. It has stable chemical properties and good compatibility with cationic surfactants.

[0028] The dodecylbenzene sulfonate in the sodium dodecylbenzene sulfonate solution can be connected with the calcium ions dissolved on the surface of fly ash, silica ash and basalt fiber. Specifically, fly ash, silica ash and basalt fiber are mixed with the sodium dodecylbenzene sulfonate solution, and the negatively charged dodecylbenzene sulfonate in the solution is combined with the calcium ions dissolved on the surface of fly ash, silica ash and basalt fiber, so that the surface of fly ash, silica ash and basalt fiber is activated, and materials with the same charge repel each other and separate from each other, so they are not easy to agglomerate. The reaction principle is as shown in formula (1):

[0029] [C 12 H 22 (CH3)2(C6H4)SO3] - +Ca 2+ →[CaC 12 H 22 (CH3)2(C6H4)SO3] + (1).

[0030] The concentration of dodecyl dimethyl benzyl ammonium bromide solution is 200-280 mg / L, and the most preferred concentration is 240 mg / L. It has stable chemical properties and good compatibility with anionic surfactants.

[0031] The dodecyl dimethyl benzyl ammonium ions in the dodecyl dimethyl benzyl ammonium bromide solution can be connected with the silicate ions dissolved on the surface of the fly ash. The surface modification method of the fly ash hollow microspheres is chemical plating, specifically, the fly ash hollow microspheres after ball milling are mixed with the dodecyl dimethyl benzyl ammonium bromide solution, and the positively charged dodecyl dimethyl benzyl ammonium in the solution is combined with the silicate ions dissolved on the surface of the fly ash hollow microspheres, so that the surface of the fly ash hollow microspheres is activated, and the materials with the same charge repel each other and separate from each other, so they are not easy to agglomerate. The reaction principle is shown in formula (2):

[0032]

[0033] Due to the mutual attraction of charges between the modified fly ash, silica ash, basalt fiber and the modified fly ash hollow microbeads, the modified fly ash, silica ash and basalt fiber tend to surround the modified fly ash hollow microbeads, and similarly, the modified fly ash hollow microbeads also tend to surround the modified fly ash, silica ash and basalt fiber, forming an ordered fiber network structure with good ductility and good compressive strength.

[0034] The pore size of fly ash hollow microbeads is controllable and can be changed. According to the density requirements of concrete and the amount of fly ash hollow microbeads added, the pore size of fly ash hollow microbeads can be adjusted to effectively control the size of pores inside concrete, and finally concrete that meets the density requirements can be obtained.

[0035] The present invention also provides a method for preparing the above-mentioned lightweight and high-ductility concrete, and the preparation method is as follows:

[0036] Step S1, weighing the raw materials, mixing fly ash, silica ash and basalt fiber, and stirring evenly to obtain composite filler A;

[0037] Step S2, mixing the sodium dodecylbenzene sulfonate solution with the composite seasoning A in step S1, adding one eighth of water, stirring evenly and drying to obtain a modified composite filler B;

[0038] The dodecyl dimethyl benzyl ammonium bromide solution is mixed with the fly ash hollow microspheres, and one eighth of water is added, stirred evenly and dried to obtain modified fly ash hollow microspheres C;

[0039] Step S3, mixing the modified composite filler B and the modified fly ash hollow microspheres C in step S2, adding cement and three quarters of water, stirring evenly, and obtaining a lightweight and high-ductility concrete.

[0040] The modified composite filler B and the modified hollow microbeads C adsorb each other due to electrostatic attraction, achieving the orderly assembly of fly ash, silica ash and basalt fibers to form an orderly fiber network structure.

[0041] Fly ash, silica fume and basalt fiber are made of pure and impurity-free raw materials that have been washed with water to prevent impurities from adhering to the surface of the raw materials and reacting with the activator to reduce the surface modification effect of the raw materials.

[0042] The fly ash hollow microspheres are made of pure impurity-free raw materials that have been washed and ball-milled. The purpose of water washing is to prevent impurities from adhering to the surface of the raw materials and reacting with dodecyl dimethyl benzyl ammonium bromide to reduce the surface modification effect of the raw materials; the purpose of ball milling is to increase the contact area of ​​the raw materials and enhance the surface modification effect.

[0043] The purpose of mixing the dodecyl dimethyl benzyl ammonium bromide solution with the fly ash hollow microspheres is to utilize the dodecyl dimethyl benzyl ammonium radicals to connect with the silicate radicals dissolved from the surface of the fly ash hollow microspheres, thereby changing the interface properties of the fly ash hollow microspheres.

[0044] The specific implementation is as follows:

[0045] Example 1

[0046] A lightweight high-ductility concrete is composed of the following raw materials: 1 part of cement, 1 part of fly ash, 0.2 part of silica fume, 0.2 part of fly ash hollow microspheres, 0.7 part of water, 0.12 part of sodium dodecylbenzene sulfonate solution, 0.14 part of dodecyl dimethyl ammonium bromide solution, and 0.6 part of basalt fiber

[0047] The preparation method of the above-mentioned lightweight and high ductility concrete is as follows:

[0048] Step S1, weighing raw materials according to proportion, mixing fly ash, silica ash and basalt fiber, stirring in a drum dry powder mixer for 20 minutes at a stirring speed of 100 r / min to obtain composite filler A.

[0049] Step S2, mixing the sodium dodecylbenzene sulfonate solution with the composite seasoning A, adding one-eighth of water, stirring in a forced flat-mouth mixer for 30 minutes at a stirring speed of 80 r / min, and then placing the stirred material in a vacuum drying oven for drying at a drying temperature of 30-80° C. for 3-8 hours, and finally obtaining a modified composite filler B.

[0050] The dodecyl dimethyl benzyl ammonium bromide solution was mixed with the fly ash hollow microspheres, and one-eighth of water was added, and the mixture was stirred in a forced flat mixer for 30 minutes at a stirring speed of 80 r / min. The stirred material was then placed in a vacuum drying oven for drying at a temperature of 30-80°C for 3-8 hours to finally obtain modified fly ash hollow microspheres C.

[0051] Step S3, mixing the modified composite filler B and the modified fly ash hollow microspheres C, adding cement and three quarters of water, stirring in a forced flat mixer for 30 minutes at a stirring speed of 80 r / min, to obtain the lightweight and high ductility concrete.

[0052] Example 2

[0053] A lightweight high-ductility concrete is composed of the following raw materials: 1.1 parts of cement, 0.9 parts of fly ash, 0.17 parts of silica fume, 0.17 parts of fly ash hollow microspheres, 0.6 parts of water, 0.08 parts of sodium dodecylbenzene sulfonate solution, 0.1 parts of dodecyl dimethyl ammonium bromide solution, and 0.5 parts of basalt fiber. The preparation process of the lightweight high-ductility concrete is as shown in Example 1.

[0054] Example 3

[0055] A lightweight high-ductility concrete is composed of the following raw materials: 1.1 parts of cement, 0.9 parts of fly ash, 0.16 parts of silica fume, 0.15 parts of fly ash hollow microspheres, 0.5 parts of water, 0.04 parts of sodium dodecylbenzene sulfonate solution, 0.06 parts of dodecyl dimethyl ammonium bromide solution, and 0.4 parts of basalt fiber. The preparation process of the lightweight high-ductility concrete is as shown in Example 1.

[0056] Example 4

[0057] A lightweight high-ductility concrete is composed of the following raw materials: 1.2 parts of cement, 0.8 parts of fly ash, 0.16 parts of silica fume, 0.1 parts of fly ash hollow microspheres, 0.4 parts of water, 0.02 parts of sodium dodecylbenzene sulfonate solution, 0.03 parts of dodecyl dimethyl ammonium bromide solution, and 0.3 parts of basalt fiber. The preparation process of the lightweight high-ductility concrete is as shown in Example 1.

[0058] In order to verify the lightweight and high ductility concrete and the preparation method of the present invention, a comparative test was also carried out:

[0059] Comparative Example 1

[0060] A concrete is composed of the following raw materials: 1 part of cement, 0.8 part of fly ash, 0.2 part of silica fume and 0.7 part of water.

[0061] The above-mentioned concrete preparation process is as follows:

[0062] Step 1: Weigh the raw materials in proportion, mix cement, fly ash, silica fume and fly ash hollow microbeads, and stir them in a drum dry powder mixer for 20 minutes at a stirring speed of 100 r / min to obtain composite filler D.

[0063] (2) The composite filler D was mixed with water and stirred in a forced flat mixer for 30 min at a stirring speed of 80 r / min to obtain concrete free of fly ash hollow microspheres and basalt fibers.

[0064] Comparative Example 2

[0065] A concrete comprises the following raw materials in parts by weight: 1 part of cement, 0.8 part of fly ash, 0.2 part of silica fume, 0.15 part of fly ash hollow microspheres, 0.7 part of water, and 0.4 part of basalt fiber.

[0066] Step 1: The above concrete preparation process is as follows:

[0067] Raw materials were weighed in proportion, cement, fly ash, silica ash, fly ash hollow microbeads and basalt fiber were mixed, and stirred in a drum dry powder mixer for 20 minutes at a stirring speed of 100 r / min to obtain composite filler E.

[0068] Step 2: Mix the composite filler E with water, and stir in a forced flat mixer for 30 minutes at a stirring speed of 80 r / min to obtain concrete without surface treatment.

[0069] like Figure 1 As shown, it is an electron microscope scanning image of the lightweight and high ductility concrete prepared in Example 3. It can be seen from the figure that fly ash and silica fume gather on the fly ash hollow microbeads to form microclusters, and at the same time, microclusters with fly ash hollow microbeads as the core gather near the basalt fibers.

[0070] The lightweight and high ductility concrete prepared in each embodiment and the concrete prepared in the comparative example were tested, and the density, compressive strength and tensile strain tests were performed, as shown in Table 1. Figure 2 and Figure 3 shown.

[0071] Table 1 Performance parameters of concrete in various embodiments and comparative examples

[0072]

[0073]

[0074] From Table 1, Figure 2 and Figure 3 It can be seen that the concrete prepared by the present invention has a low density and good ductility, and also has good compressive strength. This is because the fly ash hollow microspheres are hollow inside, and the addition of fly ash hollow microspheres effectively reduces the density of the concrete. At the same time, through surface modification, fly ash, silica fume, fly ash hollow microspheres, and basalt fibers form an ordered fiber network structure, which effectively improves the ductility of the concrete.

Claims

1. A lightweight and highly ductile concrete, characterized in that: The lightweight high-ductility concrete is composed of the following raw materials in parts by weight: 1-1.2 parts of cement, 0.8-1 parts of fly ash, 0.16-0.2 parts of silica fume, 0.1-0.2 parts of fly ash hollow microspheres, 0.4-0.7 parts of water, 0.02-0.12 parts of sodium dodecylbenzenesulfonate solution, 0.03-0.14 parts of dodecyl dimethyl benzyl ammonium bromide solution, and 0.3-0.6 parts of basalt fiber. The lightweight high-ductility concrete is prepared by the following steps: Step S1, weighing the raw materials, mixing fly ash, silica ash and basalt fiber, and stirring evenly to obtain composite filler A; Step S2, mixing the sodium dodecylbenzene sulfonate solution with the composite seasoning A in step S1, adding one eighth of water, stirring evenly and drying to obtain a modified composite filler B; The dodecyl dimethyl benzyl ammonium bromide solution is mixed with the fly ash hollow microspheres, and one eighth of water is added, stirred evenly and dried to obtain modified fly ash hollow microspheres C; Step S3, mixing the modified composite filler B and the modified fly ash hollow microspheres C in step S2, adding cement and three quarters of water, stirring evenly, and obtaining a lightweight and high-ductility concrete.

2. A lightweight and highly ductile concrete as claimed in claim 1, characterized in that: The concentration of the sodium dodecylbenzenesulfonate solution is 250-300 mg / L.

3. A lightweight and highly ductile concrete as claimed in claim 2, characterized in that: The concentration of the dodecyl dimethyl benzyl ammonium bromide solution is 200-280 mg / L.

4. A lightweight and highly ductile concrete as claimed in claim 3, characterized in that: The basalt fiber has a length of 16-25 mm, a diameter of 0.2-0.5 mm, and a tensile strength of 2000-3800 MPa.

5. The method for preparing a lightweight and high-ductility concrete according to claim 4, characterized in that: The drying temperature in step S2 is 30-80° C. and the drying time is 3-8 hours.

6. The method for preparing a lightweight and high-ductility concrete according to claim 5, characterized in that: The stirring method in step S1 is dry mixing, the equipment is a drum dry powder mixer, the stirring speed is 100r / min, and the time is 20min.

7. The method for preparing a lightweight and high-ductility concrete according to claim 6, characterized in that: The stirring method in steps S2 and S3 is wet mixing, the equipment is a forced flat-mouth mixer, the stirring speed is 80 r / min, and the time is 30 min.

Citation Information

Patent Citations

  • Light-weighted high-ductility cement-based composite material

    CN109761564A

  • Cement paste and preparation method thereof

    CN112390572A